Alcohol‐involved motor vehicle crashes and the size and duration of random breath testing checkpoints. (28th March 2021) - Morrison, Christopher N.; Kwizera, Muhire; Chen, Qixuan; Puljevic, Cheneal; Branas, Charles C.; Wiebe, Douglas J.; Peek‐Asa, Corinne; McGavin, Kirsten M.; Franssen, Shellee J.; Le, Vy K.; Keating, Michael; Williams, Frances M.; et al.
Abstract: Objective: Sobriety checkpoints have strong empirical and theoretical support as an intervention to reduce alcohol‐involved motor vehicle crashes. The purpose of this study was to examine whether checkpoint size (the number of police officers) and checkpoint duration (the amount of time in operation) affect associations between individual checkpoints and subsequent alcohol‐related crash incidence. Method: Queensland Police Service provided latitude–longitude coordinates and date and time data for all breath tests that occurred in Brisbane, Australia, from January 2012 to June 2018. We applied hierarchical cluster analysis to the latitude–longitude coordinates for breath tests, identifying checkpoints as clusters of ≥25 breath tests conducted by ≥3 breath testing devices over a duration of 3 to 8 hours. Generalized linear autoregressive moving average (GLARMA) models related counts of alcohol‐involved motor vehicle crashes to the number of checkpoints conducted per week, as well as 1 week prior and 2 weeks prior. Results: A total of 3420 alcohol‐related crashes occurred and 2069 checkpoints were conducted in Brisbane over the 6.5‐year (339‐week) study period. On average, checkpoints included a mean of 266.0 breath tests (SD = 216.3), 16.4 devices (SD = 13.7), and were 286.3 minutes in duration (SD = 104.2). Each 10 additional checkpoints were associated with a 12% decrease in crash incidence at a lag of 1 week (IRR = 0.88; 95%CI: 0.80, 0.97). We detected no differential associations according to checkpoint size or duration. Conclusions: Sobriety checkpoints are associated with fewer alcohol‐related motor vehicle crashes for around 1 week. Checkpoint size and duration do not appear to affect this relationship. Abstract : Sobriety checkpoints are an effective way to reduce drunk driving and crashing, but they are also very costly for law enforcement. Researchers at Columbia University, the University of Queensland, and the University of Iowa found that checkpoints in Brisbane, Australia, reduced alcohol‐involved crashes for around one week. The size and duration of checkpoints did not affect these relationships. These results indicate that law enforcement agencies could save costs while maintaining effectiveness by conducting smaller and shorter checkpoints.